Evaluación institucional: objetivos y criterios - Vieira Pereira, José Tomás (Revista Española de Pedagogía, 2018)
The evaluation processes must have general and specifics objectives, and the eva lua tion criteria must be clearly established for all parts of the institution that would be involved in it. Together with the goals, must be clear that institutional evaluation is a continuum process were the objectives need to be achieved and redefined periodically. This put the higher education institutions in a permanent process of self-regulation focusing on the improvement of the quality in all the activities carry out by the institution.
Keywords: evaluación institucional; Revista Española de Pedagogía